2018
DOI: 10.1002/adfm.201802201
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on High‐Capacitance Polymer Gate Dielectrics for Flexible Low‐Voltage Transistors

Abstract: The gate dielectric layer is an essential element of field‐effect transistors (FETs), large area integrated circuits, and various application electronics. Beyond basic insulation between the semiconductor layer and gate electrode, FET performance largely depends on the capacitance of the chosen insulator layer properties. Recent functional devices developments require new functionalities, such as high mechanical flexibility and stretchability in addition to basic insulating and physical properties. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
119
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 212 publications
0
119
0
Order By: Relevance
“…In the case that a single dielectric layer has inferior dielectric properties, using hybrid or multilayer dielectrics has been applied to improve the performance of OFETs as well as sensors and memory . Recently, it demonstrated that using the PMMA/polyacrylic acid (PAA) dielectric revealed extremely suppressed hysteresis and improved mobility compared to those with a pure PAA dielectric ( Figure a) .…”
Section: Optimization Of Nonideal Ofetsmentioning
confidence: 99%
“…In the case that a single dielectric layer has inferior dielectric properties, using hybrid or multilayer dielectrics has been applied to improve the performance of OFETs as well as sensors and memory . Recently, it demonstrated that using the PMMA/polyacrylic acid (PAA) dielectric revealed extremely suppressed hysteresis and improved mobility compared to those with a pure PAA dielectric ( Figure a) .…”
Section: Optimization Of Nonideal Ofetsmentioning
confidence: 99%
“…Electrolyte‐gated transistors (EGTs), including electric double layer transistors (EDLTs) and organic electrochemical transistors (OECTs), are being developed by a number of research groups for applications in sensing and printed electronics . Attractive features of EGTs are their very high transconductances and low voltage characteristics, both of which derive from the huge specific capacitance of the electrolyte gate dielectrics that they employ, which varies from ≈10 μF cm −2 in the double layer operating regime to over 100 μF cm −2 in the electrochemical regime …”
Section: Introductionmentioning
confidence: 99%
“…An alternative method is to use high‐ k polymer gate dielectrics,17 such as polyelectrolytes or derivatives of poly(vinylidene fluoride‐trifluoroethylene) (PVDF). The hygroscopic nature of polyelectrolytes present a severe disadvantage toward operational stability in ambient conditions 18.…”
mentioning
confidence: 99%
“…[14,15] However, in these devices, unreacted hydroxyl groups act as charge trapping sites that are undesirable for stable device operation [16] and large-area processing of robust and uniform ultra-thin films poses a significant challenge for scale-up of these devices. [16] An alternative method is to use high-k polymer gate dielectrics, [17] such as polyelectrolytes or derivatives of poly(vinylidene fluoride-trifluoroethylene) (PVDF). The hygroscopic nature of polyelectrolytes present a severe disadvantage toward operational stability in ambient conditions.…”
mentioning
confidence: 99%